An innovative method for improving the cyclic performance of concrete beams retrofitted with prefabricated basalt-textile-reinforced ultra-high performance concrete. (June 2023) - Esmaeili, Jamshid; Khoshkanabi, Seyed Pouya; Andalibi, Keyvan; Kasaei, Jamil
Abstract: Retrofitting reinforced concrete structures (RC) with textile reinforced concrete is an alternative material. In this paper, the primary objective is to develop a novel type of strengthening method for RC structures by utilizing prefabricated textile-reinforced concrete composites. This study examined the flexural behavior of RC beams retrofitted with prefabricated basalt textile reinforced concrete (BTRC) panels. An experimental study was conducted on five retrofitted reinforced concrete beams to demonstrate the effectiveness of this strengthening method. A cyclic four-point bending load test was performed to determine the flexural behavior of BTRC retrofitted reinforced concrete beams. Polymer concrete is used to join the BTRC composite panel, which is constructed from layers of ultra-high performance fiber reinforced concrete (UHPFRC) and basalt textile. A comparison is made between the results obtained using cast-in-situ strengthening and those obtained using textile layers. Based on the results, prefabricated BTRC strengthening method was more effective than cast-in-place strengthening in improving the loading carrying capacity of reinforced RC beams. Compared to cast-in-situ retrofitting, the flexural strength was improved by 56%. In addition, the proposed method for connecting prefabricated BTRC composites to RC beams resulted in the tensile rupture of BTRC layers. As a result, BTRC composites can improve the flexural performance of reinforced concrete beams due to their maximum capacity. This method is an effective and affordable method, and the retrofitting technique was successful. The advantages of this method may outweigh the disadvantages of other methods.